Algoritma Pencarian : Linear - az-zahra, nadya clarisa (Maliki Interdisciplinary Journal, 2025)
The linear search algorithm is a simple method for finding an element in a list or array. This method works by checking each element one by one, starting from the first until the desired element is found or all elements have been examined. Although this algorithm is easy to understand and implement, its efficiency depends on the number of elements in the list. In this paper, we will discuss the fundamental principles of the linear search algorithm, the steps for its implementation, as well as its advantages and disadvantages compared to other search algorithms. We will also include practical examples from everyday life to help illustrate this concept. With a clear understanding of this algorithm, readers are expected to apply it in various programming and data processing situations.